2019
DOI: 10.24966/rmgo-2574/100018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Female Genital Tubercular Involvement on Anti-Mullerian Hormone Secretion in Latent Genital Tuberculosis Affected Women

Abstract: Poor ovulatory response to stimulation is observed in women undergoing IVF programme who has tubercular infestation in genital tract. This is probably due to diminished ovarian function as indicated by lowering of AMH level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Datta et al ., 2019, also observed that AMH concentration was much lower in PCR positive group than PCR negative with statistical significance. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Datta et al ., 2019, also observed that AMH concentration was much lower in PCR positive group than PCR negative with statistical significance. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%